Inovasi Khulafa’ Rasyidin dalam Memelihara Orisinilitas Al-Qur’an - Aguswan Rasyid; Sadri Sadri; Lusiana Lusiana (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The Koran is one of the holy books that Allah revealed to humans. The purity of the Koran will always be preserved until the end of time. The maintenance of the purity of the Qur'an cannot be separated from the innovations created by the Rasyidin Khulafa'. This research aims to reveal the innovations and ideas of the Rasyidin khulafa' in maintaining the originality of the Koran. The results of the study show that the innovation of the Rasyidin khulafa' in maintaining the originality of the Qur'an was realized in the form of unification and codification of the Qur'an in one mushaf during the time of the caliph Abu Bakr, re-codification of the Qur'an, copying it into several manuscripts and Uniformizing the punctuation of the Qur'an during the time of Caliph Usman bin Affan and giving honors (lines) to the Qur'an during the time of Caliph Ali bin Abi Talib. It is hoped that this study can provide motivation to scholars and ulama in particular and Muslims in general to continue to innovate in Al-Qur'an studies so that Islamic teachings originating from the Al-Qur'an are felt to be relevant for all times and generations and can provide solutions. to the problems faced by the people.